Antiviral Efficacy and Safety of Molnupiravir Against Omicron Variant Infection: A Randomized Controlled Clinical Trial - Zou, Rongrong; Peng, Ling; Shu, Dan; Zhao, Lei; Lan, Jianfeng; Tan, Guoyu; Peng, Jinghan; Yang, Xiangyi; Liu, Miaona; Zhang, Chenhui; Yuan, Jing; Wang, Huxiang; et al. (Frontiers in Pharmacology, 2022)
Background: The rapid worldwide spread of the Omicron variant of SARS-CoV-2 has unleashed a new wave of COVID-19 outbreaks. The efficacy of molnupiravir, an approved drug, is still unknown in patients infected with the Omicron variant. Objective: Evaluated the antiviral efficacy and safety of molnupiravir in patients infected with SARS-CoV-2 Omicron variant, with symptom duration within 5 days. Methods: We conducted a randomized, controlled trial involving patients with mild or moderate COVID-19. Patients were randomized to orally receive molnupiravir (800 mg) plus basic treatment or only basic treatment for 5 days (BID). The antiviral efficacy of the drug was evaluated using reverse transcriptase polymerase chain reaction. Results: Results showed that the time of viral RNA clearance (primary endpoint) was significantly decreased in the molnupiravir group (median, 9 days) compared to the control group (median, 10 days) (Log-Rank P=0.0092). Of patients receiving molnupiravir, 18.42% achieved viral RNA clearance on day 5 of treatment, compared to the control group (0%) (P=0.0092). On day 7, 40.79% and 6.45% of patients in the molnupiravir and control groups, respectively, achieved viral RNA clearance (P=0.0004). In addition, molnupiravir has a good safety profile, and no serious adverse events were reported. Conclusion: Molnupiravir significantly accelerated the SARS-CoV-2 Omicron RNA clearance in patients with COVID-19. Clinical Trial Registration: chictr.org.cn ChiCTR2200056817.